Thermal design and optimization of HIAF′s medical isotope target under extreme heat flux based on a two-way fluid–structure interaction model - Xin Li; Heng Zhang; Zihao Zhang; Jianrong Zhang; Qingfeng Tang; Wei Wang; Yucui Gao; Lei Yang; Yaling Zhang (Annals of Nuclear Energy, 2026)

Synergistic room-temperature NH3 sensing: TiO2/g-C3N4 heterojunction with UV-enhanced performance for food freshness monitoring - Haineng Bai; Chenjie Wang; Yang Yu; Yiru Chen; Cheng Feng; Yunxiao Du; Yamin Feng; Weifeng Liu; Kuili Liu; Sihua Zhou; Fuqiang Guo; Qingfeng Li; et al. (Chemical Engineering Journal, 2026)

Ordered mesoporous NiGa2O4-NiO heterostructure for highly sensitive detection of low-concentration p-xylene - Chen Shao; Wu Zou; Jie Chen; Xiaoyong Lai; Xiaomei Yang; Shengzhou Cai; Xiaozhong Wang; Qingfeng Yang (Chemical Engineering Journal, 2026)

Aggregation-induced emission photosensitizers for photodynamic food packaging: Antibacterial mechanisms, material innovations, and applications - Wenxin Wang; Shutian Sun; Simin Fan; Qingfeng Yang; Dequan Zhang; Chengli Hou (Trends in Food Science & Technology, 2026)

Low-lethal and intergenerational effects of broflanilide on the diamondback moth, Plutella xylostella (L.) - Kunkun Wang; Qiqi Zhao; Chenyao Yang; Chen Shen; Qichao Zhang; Renwen Zheng; Pei Liang; Qingfeng Tang (Pesticide Biochemistry and Physiology, 2026)

Key exposure components and oxidative stress-driven health risks assessment of oil mist generated by metalworking fluids in industrial building environment - Yang Yang; Yilin Li; Yuming Zhang; Yi Wang; Yalin Liu; Ming Liu; Xudong Li; Yifan Qu; Mengdan Qiao; Qingfeng Cao (Journal of Hazardous Materials, 2026)

Lymph node-targeted H2S-self-releasing multifunctional prodrug for the dual remodeling of immunological and redox homeostasis in autoimmune uveitis - Qinjin Dai; Yuelan Wu; Wenbo Geng; Mengna Li; Wanyun Zhang; Yuxian Lai; Pei Zhang; Xiaoyue Zhang; Chunjiang Zhou; Yinuo Wang; Qingfeng Cao; Xiang Luo; et al. (Chemical Engineering Journal, 2026)

An onboard ultra-rapid orbit determination strategy for LEO satellite utilizing spaceborne GNSS data - Peng Luo; Yezhi Song; Xiaogong Hu; Qingfeng Wu; Jianhua Yang; Kai Li; Chengpan Tang; Changshao Chen (Advances in Space Research, 2026)

Spatial and temporal evolution of the groundwater depth and indirect effects during the spring irrigation period in the Hetao Irrigation District - Yi Zhao; Haibin Shi; Xianyue Li; Shuya Yang; Haoqi Han; Yunlei Dong; Qingfeng Miao; Jianwen Yan; Cong Hou; Xu Dou (Irrigation Science, 2026)

A star’s death by a thousand cuts: the runaway periodic eruptions of AT2023uqm - Yibo Wang; Tinggui Wang; Shifeng Huang; Jiazheng Zhu; Ning Jiang; Wenbin Lu; Rongfeng Shen; Shiyan Zhong; Dong Lai; Yi Yang; Xinwen Shu; Tianyu Xia; et al. (Science Bulletin, 2026)

Ecosystem collapses in Southwest China revealed by stalagmite records during the Mid-to-Late Holocene - Shaohua Yang; Chuntong He; Shitao Chen; Qingfeng Shao; Ye Zhu; Lei Lu; Hongwei Yin; Yijia Liang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Exploring the polymorphism of foxtail millet proteins and the mechanisms of activity variations driven by varietal differences - Zeyu Peng; Jia Cao; Hongyue Zhao; Bowen Yang; Jianjun Cheng; Qingfeng Ban (Food Research International, 2026)

Complex conjugate faulting of the 2024–2025 Wushi-Akqi (South Tianshan) earthquake sequence constrained by InSAR observations - Jiuyuan Yang; Huaiyang Zhang; Yangmao Wen; Zhenjie Yao; Qingfeng Hu (Advances in Space Research, 2026)

Contrasting response of the Asian Summer monsoon to bipolar climates and implications for ice core chronology during Marine Isotope Stages 5c-a inferred from stalagmite record, Central China - Zhenjun Wang; Shitao Chen; Yongjin Wang; Yalan Zeng; Li Wu; Yijia Liang; Gongzhe Chen; Zhenqiu Zhang; Shaohua Yang; Chunsheng Hu; Peng Sun; Qingfeng Shao; et al. (Global and Planetary Change, 2026)

Ultrasensitive and selective detection of metronidazole residues in milk powder using a novel 3D MOF fluorescent sensor - Xuanqi Zhang; Guiling Gao; Xiaoyong Lai; Qin Hou; Yi Li; Zhiyong Teng; Xiaozhong Wang; Xiao Zhang; Qingfeng Yang (Food Chemistry, 2026)

Multiple benefits of biochar for remediating contaminated mining soils: heavy metal stabilization, carbon sequestration, and ecological function restoration - Yibo Cheng; Weiying Feng; Yu Wang; Fang Yang; Qingfeng Miao; Chiamin Ho; Yaoqiang Huo; Haiqing Liao (Chemical Engineering Journal, 2026)

In situ gas-foaming strategy to construct nitrogen-doped porous hollow carbon spheres for ultra-broadband microwave absorbers - Youjun Jiang; De-Zhuang Wang; Mengqian Zhang; Yuerong Li; Yazhong Chen; Jun Yang; Xianlong Zhang; Qingfeng Liu; Xueping Wu (Chemical Engineering Journal, 2026)

Microbial Community Structure, Rather Than Diversity, Predicts Plant Yield Under Global Change - Xu Xu; Jie Liu; Shicong Chen; Shanshan Liu; Menghui Dong; Qingfeng Xu; Peiyao Yang; Ting Sun; Longzheng Wang; Hemu Zhang; Yang Yang; Qirong Shen; et al. (Global Change Biology, 2026)
Under global change, terrestrial plants adjust their physiological metabolism alongside adaptive restructuring of rhizosphere microbial communities, yet the mechanistic links between plant phenotypic plasticity and microbial consortia remain unclear. Here, we conducted a meta‐analysis of 272 global‐change experimental comparisons and found that, among all global change factors examined, nitrogen addition exerted the strongest effects on both plant yield and microbial community assembly. Plant adaptive responses were more strongly associated with shifts in microbial community structure than with changes in alpha diversity. Microbial community structure reorganization was associated with increased soil carbon availability, whereas higher local microbial beta diversity constrained the magnitude of structural change. Based on a reanalysis of published amplicon sequencing datasets, we found that more stable and complex microbial networks, enriched with Proteobacteria and Actinobacteria, were associated with higher plant yield. These findings underscore plant‐microbe co‐adaptation under global change, highlighting microbial community structure as a key mediator linking soil environmental shifts to plant adaptive performance.

Ethyl ferulate attenuates allergic asthma via inhibiting macrophage M2 polarization through STAT6/IRF4 pathway - Longlong Ge; Weizhen Chen; Shuguang Han; Huan Yang; Mingchen Du; Shengpeng Li; Xinran Bai; Peilin Zhao; Dan Chen; Qingfeng Pang; Yaxian Wu (Inflammation Research, 2026)

Study on the effects of ultraviolet inactivation in the process of gynogenetic development of grass carp eggs induced by mirror carp sperm - Wangchao He; Yu Sun; Kuo Chen; Junwen Liang; Binchao Liang; Xinyan Zhu; Qingfeng Liu; Yang Chen; Jialin Tang; Fuzhong Yang; Chun Zhang; Bo Chen; et al. (Aquaculture, 2026)

Interfacial engineering of graphene oxide with heterostructure to construct tortuous pathways in polylactic acid multilayers as barrier packaging - Qingfeng Yang; Xiaotong Sun; Dequan Zhang; Ming Tian; Wenxin Wang; Jinkai Pang; Xin Li; Wei Yang; Chengli Hou (Food Packaging and Shelf Life, 2026)

Evolution of plumes from a composite plate–cylinder heat source under buoyancy–shear driven conditions - Ningbin Zhu; Yang Yang; Mengdan Qiao; Yi Wang; Qingfeng Cao; Yong Cui; Yuming Zhang; Sikang Li (Building and Environment, 2026)

Flow pattern regime of ventilated cavity around an axisymmetric body under a varying incoming flow velocity: an experimental study - Zichao Shao; Liang Hao; Yue Wu; Taotao Liu; Qingfeng Yang; Dongning Fan; Biao Huang (Ocean Engineering, 2026)

Resistance characteristics of irregular exhaust hoods and inverse design based on airflow distribution in rolling mills - Qingfeng Cao; Yang Yang; Zhaolan Zhang; Yi Wang; Kangning Xiong; Yong Cui; Yuming Zhang; Sikang Li; Ning Lei (Journal of Cleaner Production, 2026)

Synergistic optimization of filter bag arrangement and shape for vortex suppression flow equalization and resistance reduction in a straight-through baghouse dust collector - Qingfeng Cao; Yang Yang; Yi Wang; Kangning Xiong; Ningbin Zhu; Yong Cui; Yuming Zhang; Sikang Li (Journal of Cleaner Production, 2026)

Effects of protein structure and proteomics on the moisture migration in rice with milling degrees - Jia Cao; Zeyu Peng; Lina Sun; Ruobing Jia; Bowen Yang; Jianjun Cheng; Qingfeng Ban; Huan Wang (Food Research International, 2026)

Modulation of postmortem glycolysis in pork by electrostatic field: Roles of pyruvate kinase and myofibrillar protein phosphorylation - Yuqian Xu; Dequan Zhang; Martine Schroyen; Xin Li; Qingfeng Yang; Chengli Hou (Food Chemistry, 2026)

High-performance, durable bamboo conductive macrofibers based triboelectric nanogenerator for stable harvesting water wave energy - Jiaqi Liao; Qingyu Meng; Wenwen Zhu; Wenhao Xu; Yang Peng; Shitao Shi; Zewei Ye; Chencong Liu; Qingfeng Sun; Xiaoping Shen (Chemical Engineering Journal, 2026)

Regular and mechanism of millennial scale weak monsoon events during the late MIS7 to early MIS6.5 period - Shaohua Yang; Shitao Chen; Yongjin Wang; Bin Zhao; Yijia Liang; Zhenjun Wang; Zhenqiu Zhang; Quan Wang; Qingfeng Shao; Lei Lu; Chuan-Chou Shen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Influence of varying oxygen transmission rates in heat-shrinkable packaging on the quality of beef during 90 days of chilled storage - Ming Tian; Jintao Jia; Dequan Zhang; Xiaotong Sun; Jiarui Li; Chaoqiao Zhu; Wei Yang; Xin Li; Qingfeng Yang; Chengli Hou (Meat Science, 2026)

Separation and enrichment of platinum from spent petroleum reforming catalysts via carrier-directed dissolution under alkaline conditions - Qingfeng Xiong; Han Yang; Lang Liu; Jibiao Han; Yu Shen; Wenhui Ma; Yakun Zhang; Ruiling Yuan; Chao Wang (Journal of Environmental Chemical Engineering, 2026)

Polyethylene microplastics specifically drive the dissemination of ARGs: Mechanisms involving microbial community restructuring and horizontal gene transfer - Xionghao Hu; Kehong Yu; Beibei Chai; Qingfeng Tang; Xia Gao; Jiamin Wang; Zhaoyang Yan; Yang Li; Lei Zhang; Chao Wang; Xiaohui Lei; Bin Chen; et al. (Science of The Total Environment, 2026)

Childhood susceptibility to PFAS-associated endocrine disruption: NHANES age-stratified analysis and PFOS mouse model validation - Qiming Yang; Wenxin Bai; Yujun Liu; Xiuxian Huang; Bing Zou; Zubair Muhammad; Uswa Farooq; Qingfeng Zhai; Nan Liu (Reproductive Toxicology, 2026)

Texture-sweetness Co-design of dysphagia Foods:Research on the textural regulation and sweetener release mechanisms of soy protein gels by sucrose and xylitol - Yahui Du; Zengwang Guo; Chunfang Ma; Bolatkhan K. Zayadan; Qingfeng Ban; Hong Yang; Zhongjiang Wang; Hongbo Sun (Food Hydrocolloids, 2026)

General synthesis of ordered mesoporous gallate spinels with ultrathin frameworks for gas sensing and catalytic applications - Chen Shao; Jie Chen; Xiaoyong Lai; Wu Zou; Xiaomei Yang; Shengzhou Cai; Xiaozhong Wang; Qingfeng Yang (Chemical Engineering Journal, 2026)

Highly sensitive, selective and reversible detection of Fe3+ ions based on elastic cellulose nanofibrils/chitosan composite modified with colorimetric and fluorescent probe - Zhe Zhang; Congcong An; Liyun Feng; Qingfeng Yang; Ming Zhang (Carbohydrate Polymers, 2026)

Ecological responses of the largest lake-wetland system (North China Plain) to hydrological regulation and cultural eutrophication over the past 70 years - Longjuan Cheng; John P. Smol; Qi Lin; Chaoran Wei; Shuyi Yang; Dejun Wan; Qingfeng Jiang; Dongliang Ning; Bin Xue (Anthropocene, 2026)

Piezoelectric Analysis of a Hydrofoil Undergoing Vortex-Induced Vibration - Shiyan Sun; Yong Yang; Qingfeng Wang (Journal of Marine Science and Engineering, 2026)
This study numerically investigates the piezoelectric behavior of a hydrofoil under vortex-induced excitation. The fluid field, characterized by a Kármán vortex street forming around the hydrofoil, is solved using the finite volume method (FVM) based on viscous flow theory. The resulting vortex-induced pressure is then imported to compute the electric field by solving a coupled electromechanical problem within the finite element method (FEM) framework, which links the electric and strain fields. The temporal and spatial distribution of the voltage under the periodic excitation force is provided, and the affecting factors, including the attack angle and the flow velocity, are analyzed in detail.

Pressure drop reduction of filter media for oily aerosol: progress and prospects - Yong Cui; Yang Yang; Kangning Xiong; Yi Wang; Qingfeng Cao; Sikang Li; Yuming Zhang (Energy and Buildings, 2026)

Diffusion of micron-sized oil droplets accompanying short-term thermal airflow with weak buoyancy in machining intervals - Yuming Zhang; Yang Yang; Yi Wang; Jia-ning Fan; Tongtong Zhao; Jun Gao; Qingfeng Cao; Ningbin Zhu; Yong Cui (Building and Environment, 2026)

Preliminary application of synchrotron time-resolved SAXS in in-situ study of dust explosion - Haijuan Wu; Jiahao Liu; Xiaolan Ji; Wenmin Li; Longlong Yang; Yingfeng Sun; Qingfeng Qin; Zhihong Li; Xiong Cao; Yixin Zhao (Fuel, 2026)

The 9.2 ka event during the early Holocene recorded by a stalagmite from Dongge Cave - Chuntong He; Bin Zhao; Yongjin Wang; Kan Zhao; Shaohua Yang; Qingfeng Shao; Hai Cheng; Yijia Liang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Variable-intensity electrostatic fields inhibit specific spoilage organisms in fresh meat: Mechanisms and antimicrobial efficacy - Su Wang; Debao Wang; Xiangyuan Wen; Yuqian Xu; Dongmei Leng; Qingfeng Yang; Chengli Hou; Xin Li; Dequan Zhang (Food Chemistry, 2025)

Incorporating quercetin nanocrystals in chitosan-polyvinyl alcohol composite film with cinnamon essential oil loaded Pickering emulsions for enhanced controlled release properties - Simin Fan; Dequan Zhang; Qingfeng Yang; Chaoqiao Zhu; Aurore Richel; Marie-Laure Fauconnier; Cheng Li; Ming Tian; Xin Li; Chengli Hou (Food Packaging and Shelf Life, 2025)

Study on the Influence of Geological Fault Structure on the Energy Evolution of Rockbursts - Shoujian Peng; Chaolong Qin; Qingfeng Xu; Jiang Xu; Yan Yang; Feng Jiao; Xiaoli Nong; Ming Li (Rock Mechanics and Rock Engineering, 2025)

Evidence for vertical transmission of avian reovirus in chickens - Li Chen; Lijuan Yin; Li Li; Zhiqiang Wu; Jialin Yang; Shenghua Yang; Xuesong Li; Qingfeng Zhou; Zhanxin Wang; Wencheng Lin (Veterinary Microbiology, 2025)

Chinese speleothem evidence of the early-mid Holocene transition and the instability of Asian summer monsoon - Bin Zhao; Yongjin Wang; Kan Zhao; Jianjun Yin; Quan Wang; Shaohua Yang; Qingfeng Shao; Hai Cheng; Yijia Liang (Global and Planetary Change, 2025)

Reinforcement of chitosan/ polyvinyl alcohol film by quercetin self-assembled nanocrystals for fresh meat preservation - Simin Fan; Wenxin Wang; Qingfeng Yang; Chaoqiao Zhu; Ming Tian; Aurore Richel; Marie-Laure Fauconnier; Chengli Hou; Dequan Zhang (Food Chemistry, 2025)

Mechanistic insights into metformin's anti-hyperuricemic effect: Targeting PPP/DNPB/XOD-mediated purine pathway, purinosome assembly, and gut microbiota homostasis in rats - Qiuxia Yu; Huijun Liao; Wenwen Tan; Lieqiang Xu; Guoshu Lin; Zhixuan Ai; Qingfeng Xie; Yuhong Liu; Yucui Li; Xiaobo Yang; Ziren Su; Guo Ma; et al. (Chemico-Biological Interactions, 2025)

A physics-informed neural network integrating physical mechanisms and experimental data for predicting VOCs emission rates in machining workshops - Mengdan Qiao; Yang Yang; Ningbin Zhu; Yi Wang; Sikang Li; Qingfeng Cao; Yanghui Hou; Bo Qian (Building and Environment, 2025)

Monsoon and hydroclimate evolution during Heinrich Stadial 3 as revealed by stalagmite from Central China - Zhenjun Wang; Shitao Chen; Yongjin Wang; Li Wu; Shaohua Yang; Gongzhe Chen; Zhenqiu Zhang; Yijia Liang; Qingfeng Shao; Hai Cheng; R. Lawrence Edwards (Global and Planetary Change, 2025)

In situ study of the effect of ignition delay time on the lignite dust explosion using synchrotron radiation time-resolved SAXS - Xiaolan Ji; Jiahao Liu; Haijuan Wu; Longlong Yang; Wenmin Li; Yingfeng Sun; Qingfeng Qin; Zhihong Li; Lili Dong; Yuanyang Wang; Yixin Zhao; Xiong Cao; et al. (Fuel, 2025)

Preparation of a high-strength, antibacterial, and biodegradable bio-based film through amide crosslinking and nano-reinforcement for fruit packaging - Shuguang Yang; Yile Xu; Anbo Pan; Peisheng Li; Wenwu Yang; Qingfeng Sun; Xiaochun Zhang; Yantao Xu (Chemical Engineering Journal, 2025)

Editorial Expression of Concern: HP-β-CD-PLGA nanoparticles improve the penetration and bioavailability of puerarin and enhance the therapeutic effects on brain ischemia–reperfusion injury in rats - Hai-quan Tao; Qingfeng Meng; Ming-hui Li; Hui Yu; Mei-fang Liu; Dan Du; Shou-li Sun; Hai-cheng Yang; Yan-ming Wang; Wei Ye; Li-zhuang Yang; Da-ling Zhu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Deglacial and Holocene precipitation seasonality on the central Tibetan Plateau - Qingfeng Ma; Liping Zhu; Junbo Wang; Jianting Ju; Ruimin Yang; Yong Wang; Xinmiao Lü (Journal of Hydrology, 2025)

The long-term environmental evolution of an urban lake in the highly developed Yangtze River Delta - Zhenglan Fu; Longjuan Cheng; Qingfeng Jiang; Jiali Zhang; Xinyue Chen; Shuyi Yang; Xinyuan Gao; Xiang Kuai; Dejun Wan; Dongliang Ning; Bin Xue (Journal of Geographical Sciences, 2025)

Assessment of the immune-developmental toxicity risk of the hygienic insecticide dimefluthrin in zebrafish (Danio rerio) model - Ruirui Li; Yang Yu; Wenxuan Cheng; Qingfeng Li; Wenping Xu; Jiagao Cheng; Liming Tao; Yang Zhang (Journal of Environmental Management, 2025)

Review of biological algal fertilizer technology: Alleviating salinization, sequestering carbon, and improving crop productivity - Siyao Dai; Weiying Feng; Fanhao Song; Tingting Li; Yingru Tao; Fang Yang; Qingfeng Miao; Pengcheng Duan; Haiqing Liao; Haibin Shi; José Manuel Gonçalves; Isabel Maria Duarte (Bioresource Technology, 2025)

Evaporation and settling of semi-synthetic metalworking fluid droplets in industrial buildings - Yuming Zhang; Yang Yang; Qingfeng Cao; Ningbin Zhu; Yong Cui; Yi Wang; Chaojie Wang (Building and Environment, 2025)

Mechanisms of SIRT1/SIRT3-mediated reduction of mitochondrial regeneration and inflammatory response in diabetic cerebral ischemia-reperfusion injury - Cheng Xin; Ouya Liu; Miao Sun; Ping Han; Xiaowen Li; Qingfeng Niu; Nenghong Ma; Xiao Yang; Changchun Hei; Ping Liu (Metabolic Brain Disease, 2025)

Correction: Establishing Clinically Relevant Specifications for Carbamazepine Tablets Using Physiologically Based Pharmacokinetic Modeling - Xiaofeng Wang; Longjie Li; Hongyi Yang; Qingfeng He; Xiao Zhu; Jiajing Wang; Bo Sun; Peng Liu; Xiaoqiang Xiang (The AAPS Journal, 2025)

Stretchable, controlled release of active substances, and biodegradable chitosan-polyvinyl alcohol hydrogel film for antibacterial and chilled meat preservation - Debao Wang; Chaoqiao Zhu; Qingfeng Yang; Yuqian Xu; Dequan Zhang; Daoying Wang; Fang Liu; Chengli Hou (Food Chemistry, 2025)

Sustainable nanofiber films based on polylactic acid/modified cellulose nanocrystals containing various types of polyphenols, exhibiting antioxidant activity and high stability - Chaoqiao Zhu; Qingfeng Yang; Ming Tian; Wei Yang; Chengjun Min; Simin Fan; Debao Wang; Xin Li; Dequan Zhang; Chengli Hou (Food Chemistry, 2025)

Establishing Clinically Relevant Specifications for Carbamazepine Tablets Using Physiologically Based Pharmacokinetic Modeling - Xiaofeng Wang; Longjie Li; Hongyi Yang; Qingfeng He; Xiao Zhu; Jiajing Wang; Bo Sun; Peng Liu; Xiaoqiang Xiang (The AAPS Journal, 2025)

Corrigendum to ‘What are exposure biomarkers of rare earth elements for the ionic rare earth occupational population?’ [Environ. Pollut. 345 (2024) 123499] - Qingfeng Chen; Jun Hong; Guowen Lai; Xiaobo Yang; Guoliang Chen; Na Xu; Xuewei Li; Kaibo Hu; Tianci Chen; Yang Song; Yinhua Wan (Environmental Pollution, 2025)

The Physical Simulation Study on Impact Damage Characteristics of Deep Elliptical Roadway - Qingfeng Xu; Shoujian Peng; Jiang Xu; Feng Jiao; Yan Yang; Chaolong Qin; Xiaoli Nong; Ming Li (Rock Mechanics and Rock Engineering, 2025)

Numerical Study on the Influence of Catamaran Hull Arrangement and Demihull Angle on Calm Water Resistance - Sumin Guo; Xianhe Yang; Hongyu Li; Weizhuang Ma; Qunhong Tian; Qingfeng Ma; Xin Su; Zongsheng Wang (Journal of Marine Science and Engineering, 2025)
This study investigates the WAM-V (Wave Adaptive Modular Vessel) catamaran configuration, focusing on the hydrodynamic interaction between its articulated hulls. The unique hinged connection mechanism induces a relative angular displacement between the demihulls during operation, significantly modifying the calm water resistance characteristics. Such resistance variations critically influence both vessel maneuverability and the operational effectiveness of onboard acoustic detection systems. This study using computational fluid dynamics (CFD) technology, the effects of varying demihull spacing and the angles of the demihulls on resistance were calculated. Numerical simulations were performed using STAR-CCM+, employing the Reynolds-averaged Navier–Stokes equations (RANS) method combined with the k-epsilon turbulence model. The study investigates the free surface and double body viscous flow at different Froude numbers in the range of 0.3 to 0.75. The analysis focuses on the effects of the demihull spacing ratio (BS/LPP, Demihull spacing/Length between perpendiculars) on calm water resistance. Specifically, the resistance coefficient at BS/LPP = 0.2 is on average 14% higher than that at BS/LPP = 0.5. Additionally, the influence of demihull angles on resistance was simulated at BS/LPP = 0.42. The results indicate that inner demihull angles result in higher resistance compared to outer angles, with the maximum increase in resistance being approximately 9%, with specific outer angles effectively reducing resistance. This study provides a scientific basis for optimizing catamaran design and offers valuable insights for enhancing sailing performance.

Association of PM2.5-bound multiple metals co-exposure with early cardiovascular damage: A panel study in young adults combining metabolomics - Junjie Chen; Qingfeng Zhou; Yingrong Wang; Yuting Wu; Miao Li; Haotian Wang; Guoying Zheng; Yulan Hao; Xiangke Cao; Wenqi Yang; Lei Zhang; Qian Wang (Environmental Pollution, 2025)

Novel microfluidic chips integrated with smart devices for in situ detection of foodborne pathogenic bacteria - Ruibin Hu; Wen Wang; Qingfeng Zheng; Jianhan Lin; Hua Yang (Current Opinion in Food Science, 2025)

The hygienic insecticide dimefluthrin induced neurodevelopmental deficits and behavioral disorders in zebrafish (Danio rerio) larvae - Ruirui Li; Wenping Xu; Qingfeng Li; Jiagao Cheng; Zhong Li; Liming Tao; Yang Zhang (Environmental Research, 2025)

Effect of Borehole Pressure Relief on Rockburst: Insights from Borehole Cooperative Deformation Mechanism - Dongqiao Liu; Ziqian Zhang; Jinsong Yang; Qingfeng Sun; Zhengxi Liu; Jie Sun (Rock Mechanics and Rock Engineering, 2025)

Different ploidy-level hybrids derived from female common carp × male topmouth culter - Conghui Yang; Chenghua Dai; Qiong Liu; Yating Zhu; Xuexue Huang; Xiaowei Xu; Yi Zhou; Shi Wang; Qingfeng Liu; Shaojun Liu (Aquaculture, 2025)

Water and land use in China's food systems: Exploring potential mitigation strategies - Wenjun Shi; Hanlin Liu; Yosef Steinberger; Yuanchao Hu; Yang Yang; Qingfeng Meng; Guanghui Xie (Sustainable Production and Consumption, 2025)

El Niño-Southern Oscillation signals imprinted in stalagmite δ18O from 2005 to 2017 - Jianshun Chen; Yijia Liang; Kan Zhao; Yongjin Wang; Zhenqiu Zhang; Fucai Duan; Jingwei Zhang; Qingfeng Shao; Junji Zhu; Shaohua Yang; Lian Tang; Yuqing Wang; et al. (Quaternary International, 2025)

Experimental investigation on the ventilated cavitating flow characteristics around an axisymmetric body with an unsteady ventilation - Liang Hao; Housheng Zhang; Qingfeng Yang; Taotao Liu; Biao Huang; Guoyu Wang (Ocean Engineering, 2024)

Distribution of oil mist particles and air quality improvement in the working area of the cutting workshop - Yuming Zhang; Yang Yang; Qingfeng Cao; Yi Wang; Jia-Ning Fan; Hu Chen; Xin Wang; Fei Wang; Yu Zhou; Mengfan Quan (Journal of Hazardous Materials, 2024)

Study on Impact Tendency and Damage Characteristics of Rock-Like Materials Based on Acoustic and Thermal Responses - Shoujian Peng; Yan Yang; Qingfeng Xu; Jiang Xu; Chaolong Qin; Xiaoli Nong (Rock Mechanics and Rock Engineering, 2024)

Spatial and temporal heterogeneity of soil salinity and ionic coupling relationship under the water-saving renovation of a typical irrigation district in arid and semi-arid areas - Shuya Yang; Qingfeng Miao; Haibin Shi; Yi Zhao; Xiaoyu Liu; Xin Nie; Weiying Feng; José Manuel Gonçalves; Tao Zhang; Yuxin Li; Yuli Luo (Science of The Total Environment, 2024)

Anti-tumor and anti-metastasis of water-soluble sulfated β-glucan derivatives from Saccharomyces cerevisiae - Jia Li; Mengmeng Zheng; Zhe Wang; Yang Liu; Qingfeng Niu; Han Zhou; Depeng Wang; Jike Song; Hongsheng Bi; Bin Guo; Guangli Yu; Chao Cai (Carbohydrate Polymers, 2024)

Super-hydrophilic carbonized wood-based solar steam evaporator: A novel approach to enhance freshwater generation - Hongfei Hu; Yingxuan Feng; Xinjie Chen; Linping Tian; Zhiyuan Yin; Huinan Wang; Yingying Li; Yushan Yang; Qingfeng Sun (Journal of Environmental Chemical Engineering, 2024)

A preliminary result for centralized autonomous orbit determination of gnss constellation and lunar satellite based on inter-satellite link measurements - Peng Luo; Ye-Zhi Song; Jianhua Yang; Xiaogong Hu; Chengpan Tang; Kai Li; Qingfeng Wu (GPS Solutions, 2024)

Microplastics increase the microbial functional potential of greenhouse gas emissions and water pollution in a freshwater lake: A metagenomic study - Tianyu Zhuo; Kehong Yu; Beibei Chai; Qingfeng Tang; Xia Gao; Jiamin Wang; Lixin He; Xiaohui Lei; Yang Li; Yuan Meng; Lifeng Wu; Bin Chen (Environmental Research, 2024)

Optimising microbial processes with nano-carbon/selenite materials: An eco-friendly approach for antibiotic resistance mitigation in broiler manure - Lizhi Li; Weikun Guan; Baohua Xiao; Qin He; Gangfu Chen; Jianzhong Wu; Zhigang Zhao; Feng You; Jinsheng Yang; Yue Xing; Lijun Zhou; Jinmeng Shi; et al. (Chemical Engineering Journal, 2024)

Heterogeneous feature learning network for multimodal remote sensing image collaborative classification - Xuchu Yu; Zhixiang Xue; Guopeng Yang; Anzhu Yu; Bing Liu; Qingfeng Hu (International Journal of Remote Sensing, 2024)

Modeling the Subpixel Land-Use Dynamics and Its Influence on Urban Heat Islands: Impacts of Factors and Scale, and Population Exposure Risk - Xun Liang; Song Guo; Chunyang Huang; Bingyu Wang; Yao Xiao; Jie He; Yang Li; Mengmeng Wang; Qingfeng Guan (Sustainable Cities and Society, 2024)

Effects of different cold chain logistics modes on the quality and bacterial community succession of fresh pork - Su Wang; Dequan Zhang; Qingfeng Yang; Xiangyuan Wen; Xin Li; Tongjing Yan; Rui Zhang; Wei Wang; Kumayl Hassan Akhtar; Caiyan Huang; Chengli Hou (Meat Science, 2024)

Hybrid chiral nanocellulose-cyanidin composite with pH and humidity response for visual inspection and real-time tracking of shrimp quality and freshness - Yingxuan Feng; Jian Lin; Xinjie Chen; Hao Chai; Linping Tian; Jiayi Zhang; Qingfeng Sun; Yushan Yang; Yingying Li (Food Chemistry, 2024)

Zein and tannic acid hybrid particles improving physical stability, controlled release properties, and antimicrobial activity of cinnamon essential oil loaded Pickering emulsions - Simin Fan; Qingfeng Yang; Debao Wang; Chaoqiao Zhu; Xiangyuan Wen; Xin Li; Aurore Richel; Marie-Laure Fauconnier; Wei Yang; Chengli Hou; Dequan Zhang (Food Chemistry, 2024)

Contribution of mono- and co-culture of Pseudomonas paralactis, Acinetobacter MN21 and Stenotrophomonas maltophilia to the spoilage of chill-stored lamb - Xiangyuan Wen; Dequan Zhang; James D. Morton; Su Wang; Xiaoyu Chai; Xin Li; Qingfeng Yang; Jinhuo Li; Wei Yang; Chengli Hou (Food Research International, 2024)

Acid doped branched poly(biphenyl pyridine) membranes for high temperature proton exchange membrane fuel cells and vanadium redox flow batteries - Ning Shi; Guorui Wang; Qian Wang; Lele Wang; Qingfeng Li; Jingshuai Yang (Chemical Engineering Journal, 2024)

Extracellular vesicles in plant-microbe interactions: Recent advances and future directions - Junsong Zhang; Liying Pan; Wenjie Xu; Hongchao Yang; Fuge He; Jianfeng Ma; Linlin Bai; Qingchen Zhang; Qingfeng Zhou; Hang Gao (Plant Science, 2024)

Forces driving ecological degradation in southern China during the MIS3: Natural or anthropogenic? - Qiong Chen; Xiaobo Huang; Hua Tu; Qingfeng Shao; Xiaoming Sun; Qiaofen Liu; Wei Wang; Zhongping Lai; Xiaoqiang Yang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Vertically designed high-performance and flexible thermoelectric generator based on optimized PEDOT:PSS/SWCNTs composite films - Binjie Xia; Xiao-Lei Shi; Li Zhang; Jia Luo; Wen-Yi Chen; Boxuan Hu; Tianyi Cao; Ting Wu; Wei-Di Liu; Yanling Yang; Qingfeng Liu; Zhi-Gang Chen (Chemical Engineering Journal, 2024)

What are exposure biomarkers of rare earth elements for the ionic rare earth occupational population? - Qingfeng Chen; Jun Hong; Guowen Lai; Xiaobo Yang; Guoliang Chen; Na Xu; Xuewei Li; Kaibo Hu; Tianci Chen; Yang Song; Yinhua Wan (Environmental Pollution, 2024)

Multiple thermal events recorded in the Acasta Gneiss Complex: Evidence from in-situ dating of zircon, titanite, and apatite - Qingfeng Mei; Jinhui Yang; Jinfeng Sun; Qiuli Li; Shitou Wu; Xiaoxiao Ling; Peng Peng; Hao Wang (Science China Earth Sciences, 2024)

Prevalence and distribution of antibiotic-resistant bacteria in the rhizosphere and rhizoplane of Suaeda salsa and Sporobolus alterniflorus grown in a pristine environment - Yu Wang; Fang Yang; Qianwen Liu; Lin Sun; Weihua Chen; Qingfeng Yu; Chenglong Pan; Guanhong Jiang; Xin'an Jiao; Yunzeng Zhang (Applied Soil Ecology, 2024)

Communication Management and Data Compression Algorithm Design of BeiDou Transparent Transmission Terminal for Argo Buoy - Hongyu Li; Yanjun Fan; Yicheng Wen; Yanchao Zou; Qingfeng Ma; Shaobo Yang (Journal of Marine Science and Engineering, 2024)
The Argo buoy detects marine environmental data by making profile movements in the ocean and transmits the profile detection data to the shore base through the communication terminal. However, due to the large volume of data collected from profile detections and the continuous operation of the terminal, the remote communication of buoys is characterized by lengthy communication times and significant power consumption. A low-power Beidou transparent transmission terminal is designed to solve these problems in this paper. The terminal performs low-power operation management and power management for terminal remote communication. After the end of a communication process, the microcontroller turns the Beidou module power off and enters STOP mode. Before the next communication process begins, the serial port wakes up the microcontroller, which powers up the Beidou module. Before the remote communication, the microcontroller compacts the profile detection data collected by the buoy to reduce the quantity of remote communication data. In this paper, a variety of data compression methods are used to compare the compression rate, and the best compression method is selected according to the format characteristics of the data. The results show that the Beidou transparent transmission terminal of the Argo buoy can realize low power consumption for remote communication in ocean exploration. The terminal reduces power consumption by 77.282% per communication, and the average number of remote communications for each profile detection data are reduced by 55 times. The low-power Beidou transparent transmission terminal improves the battery life and is conducive to the long-term operation of the buoy.

Oil price volatility and gold prices volatility asymmetric links with natural resources via financial market fluctuations: Implications for green recovery - Yang Li; Qingfeng Du (Resources Policy, 2024)

Ultrastrong lightweight nanocellulose-based composite aerogels with robust superhydrophobicity and durable thermal insulation under extremely environment - Yushan Yang; Baokang Dang; Chao Wang; Yipeng Chen; Kaicong Chen; Xinjie Chen; Yingying Li; Qingfeng Sun (Carbohydrate Polymers, 2024)

Lignocellulose/chitosan hybrid aerogel composited with fluorescence molecular probe for simultaneous adsorption and detection of heavy metal pollutants - Congcong An; Ming Zhang; Zhihao Xiao; Qingfeng Yang; Lijuan Feng; Siying Li; Meihui Shi (Journal of Environmental Chemical Engineering, 2023)

Correction to: Clinical Significance and Influencing Factors of Microvascular Tissue Reperfusion After Macrovascular Recanalization - Xuesong Bai; Fan Yu; Qiuyue Tian; Wei Li; Arman Sha; Wenbo Cao; Yao Feng; Bin Yang; Yanfei Chen; Peng Gao; Yabing Wang; Jian Chen; et al. (Translational Stroke Research, 2023)

Biotechnology Remediation and Environmental Behavior of Microplastics in Soils: A Review - Weiying Feng; Yuxin Deng; Yingnan Cao; Jing Liu; Yunping Han; Jianguo Liu; Qingfeng Miao; Fang Yang; Ying Zhu; John P. Giesy (Reviews of Environmental Contamination and Toxicology, 2023)

nZnO-based graphene/graphene oxide compounds inhibit methane metabolic pathways and lower the development of antibiotic resistance genes and virulence factors - Haibo Zhang; Lizhi Li; Qingfeng Xing; Jia Chen; Yihao Fan; Luo Dan; Yuhong Zhong; Yang Wang; Dongsheng Guo; Weikun Guan; Cheng Zhang (Journal of Cleaner Production, 2023)

Quantitative proteomics analysis on the meat quality of processed pale, soft, and exudative (PSE)-like broiler pectoralis major by different heating methods - Tianyi Yang; Yamin Yang; Peng Zhang; Weitao Li; Qingfeng Ge; Hai Yu; Mangang Wu; Lidong Xing; Zhiyu Qian; Fan Gao; Rui Liu (Food Chemistry, 2023)

Development of electrospun fish gelatin film containing lauroyl arginate ethyl and its application in large yellow croaker (Pseudosciaena crocea) preservation - Qingfeng Dong; Lan Yang; Leiwen Xiang; Yueliang Zhao; Li Li (Food Control, 2023)

Zinc/carbon nanomaterials inhibit antibiotic resistance genes by affecting quorum sensing and microbial community in cattle manure production - Lizhi Li; Weikun Guan; Yihao Fan; Qin He; Dongsheng Guo; An Yuan; Qingfeng Xing; Yang Wang; Ziqin Ma; Jian Ni; Jia Chen; Qilong Zhou; et al. (Bioresource Technology, 2023)

Fabrication of Supramolecular System Derived from Poly β-cyclodextrin Coupling Quinoline Dderivative and Its Fluorescence Sensing of Zinc Ion in Pure Water Environment - Wenping Zhu; Yinlong Chen; Zengchen Liu; Weijie Yang; Yanxia Li; Yahong Chen; Qingfeng Li; Yali Cui; Baodui Wang (Journal of Fluorescence, 2023)

Ensemble data assimilation for open channel water level forecasting under flow disturbances: A synthetic data study - Lingzhong Kong; Ruibin Chen; Hongwu Tang; Saiyu Yuan; Qian Yang; Qingfeng Ji (Journal of Hydrology, 2023)

Comparison of spatiotemporal burial and contamination of heavy metals in core sediments of two plateau lakes with contrasting environments: implication for anthropogenic-driven processes - Xiaolei Wang; Qingfeng Jiang; Zihan Zhao; Ximou Han; Jinliang Liu; Qun Liu; Bin Xue; Hao Yang (Environmental Monitoring and Assessment, 2023)

Insecticidal potential of a Consolida ajacis extract and its major compound (ethyl linoleate) against the diamondback moth, Plutella xylostella - Jun Peng; Zihan Chen; Xueqian Chen; Renwen Zheng; Sihan Lu; Muhammad Seyab; Fan Yang; Qianqian Li; Qingfeng Tang (Pesticide Biochemistry and Physiology, 2023)

Millennial-scale changes in the Asian monsoon during the MIS12 period as recorded by a Chinese stalagmite - Shaohua Yang; Shitao Chen; Yongjin Wang; Qingfeng Shao; Liangcheng Tan; Zhenqiu Zhang; Kan Zhao; Zhenjun Wang; Yijia Liang; Xiumin Zhai; Chuan-Chou Shen; R. Lawrence Edwards (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Clinical Significance and Influencing Factors of Microvascular Tissue Reperfusion After Macrovascular Recanalization - Xuesong Bai; Fan Yu; Qiuyue Tian; Wei Li; Araman Sha; Wenbo Cao; Yao Feng; Bin Yang; Yanfei Chen; Peng Gao; Yabing Wang; Jian Chen; et al. (Translational Stroke Research, 2023)

Short-term Dietary Selenium Deficiency Induced Liver Fibrosis by Inhibiting the Akt/mTOR Signaling Pathway in Rats - Lichun Qiao; Xue Lin; Yan Zhao; Qingfeng Wang; Haobiao Liu; Mei You; Qian Yuan; Zhihao Yang; Wenming Bian; Jiaxin Liu; Ziwei Guo; Jing Han (Biological Trace Element Research, 2023)

Flexible and mechanically strong MXene/cellulose-lamellae sheets for electromagnetic interference shielding - Yushan Yang; Kaicong Chen; Baokang Dang; Chao Wang; Yipeng Chen; Ming Liu; Yingying Li; Xiaochun Zhang; Qingfeng Sun (Chemical Engineering Journal, 2023)

Two-century sediment records of atmospheric mercury variations in North China and their relations with regional and global emissions - Dejun Wan; Handong Yang; Zhangdong Jin; Lei Song; Dongliang Ning; Longjuan Cheng; Qingfeng Jiang (Environmental Science and Pollution Research, 2023)

Study on the optimal conditions of ultrasonic strengthening phosphogypsum storage and solidification of CO2 - Yu Ma; Jianjun Sheng; Tianyu Li; Cheng Yang; Qingfeng Xiao; Rulan Yang (Sustainable Chemistry and Pharmacy, 2023)

Study on time effect of acidified pulverized coal micro components and discussion on mathematical correlation of influencing factors - Qingfeng Xu; Shoujian Peng; Jiang Xu; Feng Jiao; Liang Cheng; Li Jia; Hailin Yang; Yan Yang; Rulin Liu; Seeram Ramakrishna (Fuel, 2023)

Purification technology of oil mist in industrial buildings: A review - Yang Yang; Hu Chen; Qingfeng Cao; Mengdan Qiao; Yi Wang; Jia-Ning Fan; Chunhui Yang; Bo Pan; Xin Wang; Fei Wang; Wenchao Ju; Yu Zhou (Building and Environment, 2023)

Analysis of groundwater flow through low-latitude alpine permafrost by model simulation: a case study in the headwater area of Yellow River on the Qinghai-Tibet Plateau, China - Shuhui Gao; Huijun Jin; Qingbai Wu; Victor F. Bense; Dongliang Luo; Qingfeng Wang; Yuzhong Yang; Wenwen Chang (Hydrogeology Journal, 2023)

Identification of DNA methylation and genetic alteration simultaneously from a single blood biopsy - Xiaomin Chen; Jiahui Liu; Jun Li; Yinpeng Xie; Zichen Yu; Lu Shen; Qingfeng Liu; Wei Wu; Qiang Zhao; Haoxiang Lin; Gaotong Liu; Qiuping Luo; et al. (Genes & Genomics, 2023)

Advanced nitrogen removal performance and microbial community structure of a lab-scale denitrifying filter with in-situ formation of biogenic manganese oxides - Qingfeng Cheng; Zongyang Liu; Yang Huang; Shanshan Feng; Erdeng Du; Mingguo Peng; Jie Zhang (Journal of Environmental Management, 2023)

Enhanced remediation of phenanthrene in water and soil by novel biochar-immobilized bacterial microspheres - Kai Wang; Yang Sun; Dongyun Chen; Qingfeng Xu; Najun Li; Hua Li; Jianmei Lu (Chemical Engineering Journal, 2023)

Experimental and numerical study on the dynamic behavior of concrete-filled double steel tubular T-joint under impact loading - Qingfeng Yan; Jigang Zhang; Feifei Liu; Zhehao Ma; Guoliang Zhao; Chi Gu; Hanyu Song; Yang Zhao (Ocean Engineering, 2023)

Construction of g-C3N4 with three coordinated nitrogen (N3C) vacancies for excellent photocatalytic activities of N2 fixation and H2O2 production - Yanjun Xue; Chaoqun Ma; Qingfeng Yang; Xinyu Wang; Shanna An; Xiaoli Zhang; Jian Tian (Chemical Engineering Journal, 2023)

SWCNTs/Ag2Se film with superior bending resistance and enhanced thermoelectric performance via in situ compositing - Qin-Xue Hu; Wei-Di Liu; Li Zhang; Wei Sun; Han Gao; Xiao-Lei Shi; Yan-Ling Yang; Qingfeng Liu; Zhi-Gang Chen (Chemical Engineering Journal, 2023)

Epoxy-functionalized polyethyleneimine modified epichlorohydrin-cross-linked cellulose aerogel as adsorbents for carbon dioxide capture - Xinjie Chen; Jian Lin; Hanwei Wang; Yushan Yang; Chao Wang; Qingfeng Sun; Xiaoping Shen; Yingying Li (Carbohydrate Polymers, 2023)

Polyaniline@g-C3N4 derived N-rich porous carbon for selective degradation of phenolic pollutants via peroxymonosulfate activation: An electron transfer mechanism - Lidong Kou; Qingfeng Fan; Yuhong Yang; Xianying Duan; Kai Jiang; Jing Wang (Chemosphere, 2023)

An intelligent model for early kick detection based on cost-sensitive learning - Peng Chi; Li Qingfeng; Fu Jianhong; Yang Yun; Zhang Xiaomin; Su Yu; Xu Zhaoyang; Zhong Chengxu; Wu Pengcheng (Process Safety and Environmental Protection, 2023)

Mechanochemical incorporation of magnesium in iron-based composite surface for efficient hydrogenation of carbon dioxide to light olefin - Haipeng Chen; Ningning Ma; Chenwei Wang; Chenlei Liu; Xiaoyu Zhang; Weiwei Yuan; Wenqiang Li; Shixue Zhou; Qingfeng Yang; Xun Feng (Fuel, 2023)

Exploring the role of protein DJ-1 in quality of pale, soft and exudative (PSE) and red, firm and non-exudative (RFN) pork during post-mortem aging - Rui Liu; Keyue Li; Tianyi Yang; Lun Yang; Man Qin; Hai Yu; Mangang Wu; Qingfeng Ge; Wenbin Bao; Shenglong Wu (Food Chemistry, 2023)

Development of a recombinant adenovirus-vectored vaccine against both infectious hematopoietic necrosis virus and infectious pancreatic necrosis virus in rainbow trout (Oncorhynchus mykiss) - Shouhu Li; Xincang Li; Rui Yuan; Xiaoxue Chen; Shouxu Chen; Yu Qiu; Qingfeng Yang; Meng Wang; Jiangao Shi; Shuo Zhang (Fish & Shellfish Immunology, 2023)

Efficacy and Safety of Recombinant Human Prourokinase in Acute Ischemic Stroke: A Phase IIa Randomized Clinical Trial - Haiqing Song; Yuan Wang; Qingfeng Ma; Huisheng Chen; Bo Liu; Yi Yang; Jianguo Zhu; Shigang Zhao; Xiaoping Jin; Yongqiu Li; Yanyong Wang; Runxiu Zhu; et al. (Translational Stroke Research, 2022)

Hemipilia yajiangensis (Orchidoideae, Orchidaceae), a new species from western Sichuan, China, based on molecular and morphological evidence - Jiaxin Yang; Shuai Peng; Junjie Wang; Yan Wang; Shixiong Ding; Jing Tian; Guangwan Hu; Qingfeng Wang (Kew Bulletin, 2022)

Role of Melatonin in Inducing the Physiological and Biochemical Processes Associated with Heat Stress Tolerance in Tall Fescue (Festuca arundinaceous) - Mohammad Nur Alam; Li Yang; Xue Yi; Qingfeng Wang; Arif Hasan Khan Robin (Journal of Plant Growth Regulation, 2022)

In vivo symmetric multi-contrast MRI brain templates and atlas for spontaneously hypertensive rats - Yingying Yang; Quan Zhang; Jialiang Ren; Qingfeng Zhu; Lixin Wang; Zuojun Geng (Brain Structure and Function, 2022)

Comparative genomic analysis of Mycoplasma anatis strains - Qi Zhou; Kaijie Mai; Dehong Yang; Junfa Liu; Zhuanqiang Yan; Cuifen Luo; Yangtong Tan; Sheng Cao; Qingfeng Zhou; Li Chen; Feng Chen (Genes & Genomics, 2021)

Distinct methylome patterns contribute to ecotypic differentiation in the growth of the storage organ of a flowering plant (sacred lotus) - Hui Li; Xingyu Yang; Qingfeng Wang; Jinming Chen; Tao Shi (Molecular Ecology, 2021)
DNA methylation is an epigenetic modification involved in phenotypic diversity, plant development, and environmental responses. However, the mechanisms of DNA methylation underpinning the adaption of lotus ( Nelumbo nucifera ) ecotypes to high and low latitudes remain unsolved, especially adaptive evolution of their storage organs. Tropical and temperate lotus ecotypes have thin and enlarged rhizomes which are adapted to low and high latitudes, respectively. Here, we investigated the DNA methylomes and transcriptomes of rhizomes of the temperate and tropical lotus to address this issue. Compared with that of the tropical lotus, the DNA of the temperate lotus was significantly more hypermethylated, indicating an increase in global DNA methylation in the lotus, with rhizome enlargement. Meanwhile, genes associated with differentially methylated regions in their promoters tended to be differentially expressed between the two ecotypes. Interestingly, the genes with their expression negatively correlated with methylation levels in their promoters and genomic regions displayed significantly higher transposon coverage, while the genes showing a significant positive correlation between expression and methylation showed lesser transposon coverage. Further, we identified that DNA methylation, especially in the promoter region, was significantly correlated with the expression of many starch‐biosynthetic, gibberellin‐, and brassinosteroid‐signalling genes associated with rhizome differentiation. Overall, our study unveiled that distinct global and local methylation patterns between the two lotus ecotypes contribute to their expression differences and adaptive phenotypic divergence of their storage organs, highlighting the role of DNA methylation in shaping the ecotypic differentiation of lotus.

Study on dynamic damage characteristics of coal under alternating hydraulic pressure - Qingfeng Xu; Yanbin Yu; Rulin Liu; Weimin Cheng; Haotian Yang (Bulletin of Engineering Geology and the Environment, 2021)

Characterization, identification and evaluation of a novel wheat-Agropyron cristatum (L.) Gaertn. disomic addition line II-30-5 - Qingfeng Li; Yuqing Lu; Cuili Pan; Zhangjun Wang; Fenglou Liu; Jinpeng Zhang; Xinming Yang; Xiuquan Li; Weihua Liu; Lihui Li (Genetic Resources and Crop Evolution, 2020)

Correction to: MiR-96 promotes apoptosis of nucleus pulpous cells by targeting FRS2 - Xiaoxia Yang; Hengping Liu; Qingfeng Zhang; Kan Liu; Dong Yu; Yi Zhang; Zongting Shi (Human Cell, 2020)

MiR-96 promotes apoptosis of nucleus pulpous cells by targeting FRS2 - Xiaoxia Yang; Hengping Liu; Qingfeng Zhang; Kan Liu; Dong Yu; Yi Zhang; Zongting Shi (Human Cell, 2020)

Assessing impacts of climate change on habitat suitability of Coregonus ussuriensis and other coldwater fishes in northern China - Baoxiu Xing; He Chen; Qingfeng Chen; Yan Zhang; Zifang Liu; Zhao Yang (Environmental Science and Pollution Research, 2019)

Different pollutant removal efficiencies of artificial aquatic plants in black-odor rivers - Qingfeng Chen; Zhao Yang; Kemei Qi; Changsheng Zhao (Environmental Science and Pollution Research, 2019)

Hydrothermal variations in soils resulting from the freezing and thawing processes in the active layer of an alpine grassland in the Qilian Mountains, northeastern Tibetan Plateau - Qingfeng Wang; Qianqian Yang; Hong Guo; Xiongxin Xiao; Huijun Jin; Lili Li; Tingjun Zhang; Qingbai Wu (Theoretical and Applied Climatology, 2019)

Performance and microbial community profiles in pilot-scale biofilter for ammonia, iron and manganese removal at different dissolved oxygen concentrations - Qingfeng Cheng; Yang Huang; Lichao Nengzi; Jianying Liu; Jie Zhang (World Journal of Microbiology and Biotechnology, 2019)

Geochemistry of pyrite and chalcopyrite from an active black smoker in 49.6°E Southwest Indian Ridge - Bo Yuan; Yaomin Yang; Hongjun Yu; Yuexia Zhao; Qingfeng Ding; Jichao Yang; Xin Tang (Marine Geophysical Research, 2018)

Marker-assisted backcrossing of lcyE for enhancement of proA in sweet corn - Ruichun Yang; Zhiguang Yan; Qingfeng Wang; Xiaoqin Li; Faqiang Feng (Euphytica, 2018)

Brucella abortus phosphoglyceromutase and dihydrodipicolinate reductase induce Th1 and Th2-related immune responses - Zhiqiang Li; Hui Zhang; Jinliang Zhang; Li Xi; Guangli Yang; Shuli Wang; Qingfeng Zhou; Xiaogen Zhang; Junbo Zhang (World Journal of Microbiology and Biotechnology, 2018)

Associations of MMP-2 −1306 C/T and MMP-9 −1562 C/T polymorphisms with breast cancer risk among different populations: a meta-analysis - Meng Han; Qingfeng Yang; Kai Feng; Rongping Li; Jia Ren; Liguang Wei (Genes & Genomics, 2017)

Heme oxygenase-1 protects spinal cord neurons from hydrogen peroxide-induced apoptosis via suppression of Cdc42/MLK3/MKK7/JNK3 signaling - Siyuan Wang; Tao Zhang; Zhen Yang; Jianhua Lin; Bin Cai; Qingfeng Ke; Wenbin Lan; Jinxing Shi; Shiqiang Wu; Wenping Lin (Apoptosis, 2017)

Spatiotemporal variations in volume of closed lakes on the Tibetan Plateau and their climatic responses from 1976 to 2013 - Ruimin Yang; Liping Zhu; Junbo Wang; Jianting Ju; Qingfeng Ma; Falko Turner; Yun Guo (Climatic Change, 2017)

Erratum to: Molecular characteristics of the ompA gene of serotype B Chlamydia trachomatis in Qinghai Tibetan primary school students - Xue Li; Shaoya Zhang; Qingfeng Liang; Mei Wang; Ailian Hu; Xiuyuan Li; Benshan Yang; Mingxin Zhang; Ningli Wang; Xinxin Lu (Science China Life Sciences, 2016)

Characteristics of pathogenic microorganisms found in 99 cases of conjunctivitis from the Qinghai Tibetan area - Benshan Yang; Xiuyuan Li; Qingfeng Liang; Shaoya Zhang; Shijing Deng (Science China Life Sciences, 2016)

Molecular characteristics of the ompA gene of serotype B Chlamydia trachomatis in Qinghai Tibetan primary school students - Xue Li; Shaoya Zhang; Qingfeng Liang; Mei Wang; Ailian Hu; Xiuyuan Li; Benshan Yang; Mingxin Zhang; Ningli Wang; Xinxin Lu (Science China Life Sciences, 2016)

Pediastrum sensu lato (Chlorophyceae) assemblages from surface sediments of lakes and ponds on the Tibetan Plateau - Falko Turner; Liping Zhu; Xinmiao Lü; Ping Peng; Qingfeng Ma; Junbo Wang; Juzhi Hou; Qiuqi Lin; Ruimin Yang; Peter Frenzel (Hydrobiologia, 2016)

Enhancement of tocopherols in sweet corn by marker-assisted backcrossing of ZmVTE4 - Faqiang Feng; Qingfeng Wang; Chen Liang; Ruichun Yang; Xiaoqin Li (Euphytica, 2015)

Cystic olfactory ensheathing cell tumor: a case report - Xuchen Qi; Yingfeng Wan; Qingfeng Yan; Yirong Wang; Shuxu Yang (Acta Neurologica Belgica, 2015)

A genome-wide identification and characterization of mircoRNAs and their targets in ‘Suli’ pear (Pyrus pyrifolia white pear group) - Qingfeng Niu; Minjie Qian; Guoqin Liu; Fengxia Yang; Yuanwen Teng (Planta, 2013)

QTL mapping for the tocopherols at milk stage of kernel development in sweet corn - Faqiang Feng; Feng Deng; Peng Zhou; Jianbin Yan; Qingfeng Wang; Ruichun Yang; Xiaoqin Li (Euphytica, 2013)

Closing the yield gap could reduce projected greenhouse gas emissions: a case study of maize production in C hina - Zhenling Cui; Shanchao Yue; Guiliang Wang; Qingfeng Meng; Liang Wu; Zhiping Yang; Qiang Zhang; Shiqing Li; Fusuo Zhang; Xinping Chen (Global Change Biology, 2013)
Although the goal of doubling food demand while simultaneously reducing agricultural environmental damage has become widely accepted, the dominant agricultural paradigm still considers high yields and reduced greenhouse gas ( GHG ) intensity to be in conflict with one another. Here, we achieved an increase in maize yield of 70% in on‐farm experiments by closing the yield gap and evaluated the trade‐off between grain yield, nitrogen (N) fertilizer use, and GHG emissions. Based on two groups of N application experiments in six locations for 16 on‐farm site‐years, an integrated soil‐crop system ( HY ) approach achieved 93% of the yield potential and averaged 14.8 Mg ha −1 maize grain yield at 15.5% moisture. This is 70% higher than current crop ( CC ) management. More importantly, the optimal N rate for the HY system was 250 kg N ha −1 , which is only 38% more N fertilizer input than that applied in the CC system. Both the N 2 O emission intensity and GHG intensity increased exponentially as the N application rate increased, and the response curve for the CC system was always higher than that for the HY system. Although the N application rate increased by 38%, N 2 O emission intensity and the GHG intensity of the HY system were reduced by 12% and 19%, respectively. These on‐farm observations indicate that closing the yield gap alongside efficient N management should therefore be prominent among a portfolio of strategies to meet food demand while reducing GHG intensity at the same time.

Soil quality in east coastal region of China as related to different land use types - Qingfeng Meng; Jingsong Yang; Rongjiang Yao; Guangming Liu (Journal of Soils and Sediments, 2013)

HP-β-CD-PLGA nanoparticles improve the penetration and bioavailability of puerarin and enhance the therapeutic effects on brain ischemia–reperfusion injury in rats - Hai-quan Tao; Qingfeng Meng; Ming-hui Li; Hui Yu; Mei-fang Liu; Dan Du; Shou-li Sun; Hai-cheng Yang; Yan-ming Wang; Wei Ye; Li-zhuang Yang; Da-ling Zhu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Roles of intracellular fibroblast growth factors in neural development and functions - Xu Zhang; Lan Bao; Liu Yang; QingFeng Wu; Shuai Li (Science China Life Sciences, 2012)

Transgenic mice with overexpression of mutated human optineurin(E50K) in the retina - Qingfeng Meng; Zheng Xiao; Huiping Yuan; Fei Xue; Yuanmao Zhu; Xinrong Zhou; Binbin Yang; Jingbo Sun; Bo Meng; Xian Sun; Fang Cheng (Molecular Biology Reports, 2012)

Analysis of Nitrosamines Migration from Condoms in the Chinese Market Using a Proper Migration Experiment - Di Feng; Qingfeng Zhou; Xuelian Cheng; Jiedong Wang; Quanli Yang (Bulletin of Environmental Contamination and Toxicology, 2010)

Spatial disparity of slope farmland and food security in three gorges area - Liming Wang; Renguo Feng; Yanfeng Yang; Qingfeng Guan (Journal of Mountain Science, 2004)

Environmental emigration stress of slope farmland in the Three Gorges area - Wang Liming; Guan Qingfeng; Yang Yanfeng (Journal of Geographical Sciences, 2002)